Compressive properties of granular foams of adhesively bonded steel hollow sphere blocks - Yiatros, Stylianos; Marangos, Orestes; Votsis, Renos; Brennan, Feargal P. (My University, 2018)
Steel hollow spheres adhesively bonded together as a granular composite metal foam, is a special type of porous metal that aims to combine low weight, with ductility and energy absorption. Hollow spheres comprising steel foam shells were coated with a thermally activated epoxy in order to form different specimen geometries upon moulding and curing. The collapse propagation and energy absorption of steel hollow sphere blocks, comprising spheres of different sizes, was investigated experimentally, quantifying quasi-elastic and nonlinear properties of the steel hollow sphere assemblies in compression and comparing them with analytical and semi-empirical rules based on porous metal density and sphere packing. The results identify the initiation and nature of damage and highlight the merits of the material in absorbing high compressive deformations without significant loss of integrity.
Keywords: Crush band propagation; Metal foams; Steel hollow sphere assemblies; Compression testing